Modes of ideology and coloniality in the accounting textbook - David Mendes; Ana Carolina Pimentel Duarte Fonseca; Fernanda Filgueiras Sauerbronn (Arizona State University, 2020)
This paper aims to identify aspects of neoliberal ideology in the chapters dealing with accounting principles, in the textbook Introductory Accounting by FEA USP and in CPC00 (R2) - Conceptual Framework for Financial Reporting. To achieve the objective, we analyze the typical linguistic modes through which ideology operates, based on Thompson (2011). It is a critical and interpretative research that aims to discuss accounting education in Brazil from a decolonial perspective. The analyzed texts identified the ideological modes that legitimize, naturalize and universalize a neoliberal capitalist society and contribute to an image of accounting focused solely on the financial market, through a monological and normative approach in teaching materials. In this sense, the present study points to the need for an educational accounting policy, in addition to traditional calculations and techniques, which recognizes the role of accounting as a language, since it has its own grammar and structure that ensure the conditions for the reproduction of texts in different socio-political contexts.